SOME FACTORS INFLUENCING ON THE COLOUR ASSOCIATIONS OF THE LLETTERS (WITH ARMENIAN LETTERS EXAMPLE) - Azizyan, M. T. (Modern Psychology, 2019)
The purpose of this work is to study the combinations of color associations of letters in people aged 18 to 35 years. A new approach is considered, according to which Armenian letters give rise to color perceptions, which in turn vary depending on gender and place of residence. In the course of the study, an experiment was used, during which the test we developed was used, which is based on M. Lüscher's TEC. According to the analysis of the research results, the hypothesis of a change in the color associations of letters depending on gender and geographical factors has been partially refuted.
Keywords: Armenian letters, color, associations, scientific experiment, sex, residence